From the Stockholm Accords to communicative equations: a fresh look to public relations role in network organizations - Duarte, João (2014)
Everyday in mainstream and specialized media we find references to the many changes that network society is provoking across different sectors, changing values, reshaping professions, etc. Public Relations is not exempt from this impact. This is one of the starting points for the Stockholm Accords approved at the worldwide assembly of PR professional associations present at the Global Alliance’s World Public Relations Forum in Stockholm, Sweden, in June 2010. The accords sustain that PR concepts and practices need to evolve in order to be relevant in the new reality of network society and network organizations and they suggest that PR is more likely to evolve into a discipline whose strategic value lies in the facilitation of an effective governance of stakeholder relationships and in helping manage the new reality of “communicative organizations”. In this article I will try to conceptualize the idea of a ‘communicative equation’, understood as a basic dilemma PR professionals deal with in their daily work. In the network society, it’s not possible to sustain the traditional vision of stakeholders and issues as discrete concepts without carefully considering their dynamic inter relationships. The ‘communicative equation’ helps understand the interconnectedness between interests, problems, agendas, communicative behaviours and communicative groups, thus providing a strategic ability to design resilient and network friendly strategies.